Implementation of resource discovery mechanisms on peersim: Enabling up to one million nodes P2P simulation - Azrul Amri, Jamal; Wan Suryani, Wan Awang; Mohd Fadzil, Abdul Kadir; Azwa, Abdul Aziz (2015)
The objective of this study was to implement resource discovery mechanisms onto a Peer-toPeer (P2P) simulator. Resource discovery mechanisms such as random walk, restricted random walk, breadth-first search, intelligentBFS, depth-first search, adaptive probabilistic search, and blackboard resource discovery mechanism had been adopted onto PeerSim. The proposed implementation has enabled the simulation for resource discovery in P2P simulator which capable of running up to one million nodes. Brief information about each resource discovery techniques that are implemented onto PeerSim are discussed and presented.